A decision support system for nurse scheduling problem - Gecici, Ebru; Guler, Mehmet Guray (PAMUKKALE UNIV, 2020)
Nurses have to work in shifts to sustain continuous health services like other healthcare staff Nurses have very challenging working conditions, hence the schedules have to be prepared in a fair and balanced way, otherwise, their physical and psychological conditions can be affected negatively. Despite its importance, these schedules are prepared manually in almost all healthcare institutions. The academic studies are not sustainable since they are not transformed into decision support tools. In this study, nurse scheduling problem of cardiovascular surgery service of a hospital in Istanbul is addressed. First; a mixed integer programming model is proposed for the problem. Then a decision support system is prepared for users who has limited technical abilities. This system enables users to prepare fair and balanced shift schedules in a very short time.
Keywords: Nurse scheduling problem; Mixed integer programming; Decision support system; ALGORITHM; Engineering